2014
DOI: 10.1016/j.celrep.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Apolipoprotein Gene Cluster by a Long Noncoding RNA

Abstract: Apolipoprotein A-1 (APOA1) is the major protein component of high-density lipoprotein (HDL) in plasma. We have identified an endogenously expressed long non-coding natural antisense transcript, APOA1-AS, which acts as a negative transcriptional regulator of APOA1, both in vitro and in vivo. Inhibition of APOA1-AS in cultured cells resulted in the increased expression of APOA1, and two neighboring genes in the APO cluster. Chromatin immunoprecipitation (ChIP) analyses of a ~50Kb chromatin region flanking the AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
154
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 45 publications
1
154
0
Order By: Relevance
“…SENCR knockdown decreased myocardin al 72) identified a dendritic cell-specific lncRNA termed lnc-DC playing a critical role in the differentiation of dendritic cells from human monocytes and mouse bone marrow, a cell type playing important roles in atherosclerosis 73) . Another study has shown that lncRNA APOA1-AS function as a negative transcriptional regulator and distinct histone methylation patterns modulator of APOA1 74) , a major component of HDL particles associated with reduced atherosclerosis 75) . Former studies in human atherosclerotic plaques and carotid artery injury model of rat identified that lncRNA H19 is re-expressed 76,77) .…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…SENCR knockdown decreased myocardin al 72) identified a dendritic cell-specific lncRNA termed lnc-DC playing a critical role in the differentiation of dendritic cells from human monocytes and mouse bone marrow, a cell type playing important roles in atherosclerosis 73) . Another study has shown that lncRNA APOA1-AS function as a negative transcriptional regulator and distinct histone methylation patterns modulator of APOA1 74) , a major component of HDL particles associated with reduced atherosclerosis 75) . Former studies in human atherosclerotic plaques and carotid artery injury model of rat identified that lncRNA H19 is re-expressed 76,77) .…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…And, a recent report suggests that apo A-1 mRNA is regulated by endogenously expressed antisense RNA. 13 Several reports, however, indicate that apo A-1 levels are positively associated with increased risk of macro vascular disease and may represent an independent risk factor for CAD. 14 Also, decreased apo A-1/HDL absolute production rate could also be the cause for incidence of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ApoA-I is a major component of high-density lipoprotein in plasma, which exerts protective anti-inflammatory, anti-oxidant and anti-microbial functions, and it is important in innate immunity (21). ApoA-I is synthesized primarily in the liver (80%) and small intestine (10%) (24), and it is known to be important in reverse cholesterol transport and for promoting cholesterol efflux from tissues by acting as a cofactor for lecithin cholesterol acyltransferase (24). In a study of a cohort of >520,000 participants from 10 European countries, high serum concentrations of HDL and ApoA-I were associated with a decreased risk of colon cancer (23).…”
Section: Discussionmentioning
confidence: 99%